Evaluation of the Effect of Topical Application of Melatonin on Dental Implants Success in Terms of Implant Stability " Clinical and Radiological Study" - أسعد منذر; حسن حازم; الدالي محمـد عصام (Latakia University Journal -Medical Sciences Series, 2021)
The aim of this study was to evaluate the effect of the topical application of melatonin in dental implants in terms of implant stability. The sample consisted of 24 dental implants that were applied to 9 patients, each patient has received two implants at least. Each individual had their first implant with topical application of melatonin, and the second implant without melatonin application. Dental implants were evaluated at follow-up periods (six months, nine months) in terms of implant stability using Ostell ISQ device. The research was conducted in the Oral Minor Surgery and Implantology Clinic in the Oral and Maxillofacial department at Tishreen University Hospital. The results showed a difference between the two study groups with regards to the effect of topical application of melatonin on the success of dental implantation in terms of implant stability during the tow periods (six months, nine months), and this difference was in favor of the first group (with melatonin).